1999
DOI: 10.1021/cm990067p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Sn-Incorporated Layered Double Hydroxides and Their Thermal Evolution to Mixed Oxides

Abstract: A new series of Mg II Al III Sn IV hydrotalcite (HT)-like layered double hydroxides (LDHs) with Mg:Al:Sn ) 3:1:0 to 3:0:1 were synthesized for the first time by a simple coprecipitation method at room temperature. The physicochemical properties of both as-synthesized and their thermally decomposed products were investigated in detail by various analytical and spectroscopic methods such as powder X-ray diffraction (PXRD), chemical analysis, scanning electron microscopy (SEM), FT-IR spectroscopy, 119 Sn and 27 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
12

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 37 publications
6
50
0
12
Order By: Relevance
“…To investigate the incorporation of tetravalent cations into the LDH structure is interesting task because there is no clarity concerning incorporation of tetravalent metals in LDHs. Some of studies reported the possibility of synthesizing LDHs containing M(IV) ions [5,[19][20][21][22][23][24]. Another authors based on results of X-ray absorption spectroscopy (XAS) and Mössbauer spectroscopy [25] concluded that the M(IV) cations are segregated from LDH structure and may form amorphous M(IV) oxide-like particles.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the incorporation of tetravalent cations into the LDH structure is interesting task because there is no clarity concerning incorporation of tetravalent metals in LDHs. Some of studies reported the possibility of synthesizing LDHs containing M(IV) ions [5,[19][20][21][22][23][24]. Another authors based on results of X-ray absorption spectroscopy (XAS) and Mössbauer spectroscopy [25] concluded that the M(IV) cations are segregated from LDH structure and may form amorphous M(IV) oxide-like particles.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Mg/Alhydrotalcite (HT) is biocompatible 6 and has found pharmaceutical applications as antacid, 12 an ingredient in sustained-release pharmaceuticals containing nifedipine, 13 pharmaceutical compositions stabilizer, and in the preparation of aluminummagnesium salts of antipyretic, analgesic, and antiinflammatory drugs. As already mentioned above, hydrotalcite is also a potential host structure for intercalation of different kinds of NSAID molecules, thus exerting a controlled-drug release function.…”
Section: Introductionmentioning
confidence: 99%
“…SEM images also indicated the layered structure for both chosen samples ( Figure 18 for Mg 4 Fe-LDH, Figure 19 for Ca 3 Fe-LDH). This is fortunate, since arrangement at the atomic level is not always reflected in the morphology of the materials.…”
Section: Figure 15 X-ray Absorption Spectra Of the Ca 3 Fe-ldh Samplmentioning
confidence: 81%
“…1 It has the formula of Mg 6 Al 2 (OH) 16 3 Tetravalent cations such as Zr 4+ and Sn 4+ can also be incorporated into the layers. 4 Only one example is known of LDH structure with monovalent cation, the LiAl 2 -LDH that is. It has been speculated that the ionic radii of M(II) and M(III) and the difference between them, 5,6 as well as the solubility products 7 of M(II)(OH) 2 and M(II)CO 3 , play roles in defining the boundaries of the range of metal cations that can form LDHs.…”
Section: Literature Reviewmentioning
confidence: 99%